2021
DOI: 10.1177/1010539520986248
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With the Differences Between Self-Report Smoking and Urinary Cotinine Criteria

Abstract: During self-reporting, respondents underreport their smoking status for various reasons. We aimed to evaluate the difference between smoking status self-reporting and urinary cotinine tests in Korea respondents. Logistic regression analyses were performed to identify factors associated with the differences between self-reporting and urinary cotinine criteria. The dependent variable was the underreporting of smoking status; independent variables were sociodemographic, health status, and secondhand smoke (SHS) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In this study, the proportion of smokers seemed to be low (17.8%). This result should be interpreted with caution as this is a self-reported measure 27 . Possible assumption could be that some participants may have not reported their smoking status correctly for fear of stigma and/or discrimination.…”
Section: Smoking Behaviourmentioning
confidence: 79%
“…In this study, the proportion of smokers seemed to be low (17.8%). This result should be interpreted with caution as this is a self-reported measure 27 . Possible assumption could be that some participants may have not reported their smoking status correctly for fear of stigma and/or discrimination.…”
Section: Smoking Behaviourmentioning
confidence: 79%
“…According to the urine testing that confirmed smoking behavior, self-reported nonsmokers exposed to second-hand smoke exhibited higher rates of incorrect reporting of smoking behavior than those not exposed to second-hand smoke (28.6% vs. 9.4%); this is similar to the findings of past newly diagnosed cancer patients’ study, although the results did not reach a level of statistical significance 26 . However, a Korea research found nonsmokers' underreporting of their smoking status was positively associated with secondhand smoke 27 . The non-significant finding in this study could be owing to the female volunteer soldiers who had served in the military for a long time everyday being exposed to nearly the same background second-hand smoke.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to selecting the predictors to include in an analysis and specifying their effects (e.g., interactions), the integrity of the smoking outcome variable is important. The majority of smoking studies rely on self-report of smoking behavior, which might be affected by response bias [24][25][26]. The accuracy of the self-report appears to be population dependent, with trends of under-reporting found in certain groups, such as pregnant women [24].…”
Section: Introductionmentioning
confidence: 99%